Manual de procedimientos de la norma NTE-ISO/IEC 17025 para la acreditación de los laboratorios de alimentos de la carrera de ingeniería agroindustrial y alimentos en la Universidad de las Américas UDLA - Pinos León, Kathya Belén (2013)
This study aims to develop a NTE-ISO/IEC 17025 Standard Procedures Manual for the accreditation of the laboratory testing of food, in the degree of Agroindustrial and Food Engineering in the Americas University. The accreditation has established requirements, and it is necessary that the laboratory implements a quality management system. The purpose of the quality manual includes the procedures and formats related to each process. A plan has been developed that shows the infrastructure of the laboratory in compliance with the requirements outlined in the manual of worker security and health. With an onsite review, information was obtained on the current situation in regards to the laboratory equipment and methods that are performed. The budgeted equipment in this work was used in accordance with the test methods that we plan to establish, based on the INEN Norms that are already standardized. The Ecuadorian Accreditation Organization is the entity in charge of conducting evaluations for the respective processes.